Time-domain adaptive predistortion for nonlinear amplifiers - Yuanming Ding; Sano, A. (2004 IEEE International Conference on Acoustics, Speech and Signal Processing, 2004)
This paper is concerned with a new time-domain adaptive predistortion scheme for compensating nonlinearity of high power amplifiers (HPA) in OFDM systems. A complex Wiener-Hammerstein model (WHM) is adopted to describe the input-output relationship of an unknown HPA with linear dynamics, and a power series model with memory (PSMWM) is proposed to approximate the HPA expressed by the WHM. By using the PSMWM, the compensation input to the HPA is calculated in a real-time manner so that the linearization from the predistorter input to the HPA output can be attained even if the nonlinear input-output relation of the HPA is uncertain and changeable. The effectiveness of the proposed predistortion method is validated by numerical simulation for 64QAM-OFDM systems.